Language Monographs, Survey of Konkani in Karnataka, Goa and Maharashtra, Series-1 - Mahapatra, B.P. (Karnataka, 1971)
Introduction to the survey of konkani.
Keywords: Goa and Maharashtra; Language Monographs; Survey of Konkani in Karnataka